Functions of Yeast Hsp40 Chaperone Sis1p Dispensable for Prion Propagation but Important for Prion Curing and Protection From Prion Toxicity - Kirkland, P. Aaron (Genetics Society of America, 2011)
Replication of amyloid-based yeast prions [PSI(+)], [URE3], and [PIN(+)] depends on the protein disaggregation machinery that includes Hsp104, Hsp70, and Hsp40 molecular chaperones. Yet, overexpressing Hsp104 cures cells of [PSI(+)] prions. An Hsp70 mutant (Ssa1-21p) antagonizes propagation of [PSI(+)] in a manner resembling elevated Hsp104. The major cytosolic Hsp40 Sis1p is the only Hsp40 required for replication of these prions, but its role in [PSI(+)] curing is unknown. Here we find that all nonessential functional regions of Sis1p are dispensable for [PSI(+)] propagation, suggesting that other Hsp40’s might provide Hsp40 functions required for [PSI(+)] replication. Conversely, several Sis1p functions were important for promoting antiprion effects of both Ssa1-21p and Hsp104, which implies a link between the antiprion effects of these chaperones and suggests that Sis1p is a specific Hsp40 important for [PSI(+)] curing. These contrasting findings suggest that the functions of Hsp104 that are important for propagation and elimination of [PSI(+)] are either distinct or specified by different Hsp40's. This work also uncovered a growth inhibition caused by [PSI(+)] when certain functions of Sis1p were absent, suggesting that Sis1p protects cells from cytotoxicity caused by [PSI(+)] prions.